Information Provision in Rural Communities in Ghana: The Ashanti Region in Perspective - Boakye, Joseph (Ghana Library Journal, 2002)
In this paper the role of rural libraries in providing information to the Rural communities in the Ashanti Region has been discussed. Activities of other institutions in the Region by which they inform and educate the rural communities have also been looked at. These institutions are the Ministry of Agriculture, the Ministry of Health, tire National Commission on Civic Education (NCCE), the Information Services Department, and tire Lands Commission. Suggestions have also been offered toward6 improving upon the provision of information to tIre rural communities in the Ashanti Region.